2000
DOI: 10.1111/1467-8470.00097
|View full text |Cite
|
Sign up to set email alerts
|

Changing Fire Management in the Pastoral Lands of Cape York Peninsula of northeast Australia, 1623 to 1996

Abstract: Accounts of European explorers between 1623 and 1880 indicate that fires were lit by Aboriginal people on Cape York Peninsula in northeast Australia throughout the dry season (May–October). Diaries kept by three generations of pastoralists in the Musgrave area (1913–1952, 1953–1974 and 1976–1992) show that burning activities were largely confined to a two to six week period between May and early August. The timing of burning depended on the amount and date of cessation of wet season rainfall. More rarely, ‘sto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
60
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(61 citation statements)
references
References 18 publications
1
60
0
Order By: Relevance
“…Yet, increased particle concentrations were always detectable on the ground approximately 15 to 20 km downwind. Forest fires, common in Australia for centuries (Crowley and Garnett, 2012), can occasionally be a locally dominating source of particulate matter. Measurements of particle emission factors (Janha¨ll et al, 2010) …”
Section: Emissions From Other Sourcesmentioning
confidence: 99%
“…Yet, increased particle concentrations were always detectable on the ground approximately 15 to 20 km downwind. Forest fires, common in Australia for centuries (Crowley and Garnett, 2012), can occasionally be a locally dominating source of particulate matter. Measurements of particle emission factors (Janha¨ll et al, 2010) …”
Section: Emissions From Other Sourcesmentioning
confidence: 99%
“…Bowman and Panton (1993) similarly suggested that a shift from low intensity to high intensity fire is associated with cessation of Aboriginal fire management in coastal regions of the Northern Territory. Crowley and Garnett (2000) argued that on Cape York Peninsula the opposite has occurred, with pastoralists concentrating their burning earlier in the year than Aboriginal people.…”
Section: Introductionmentioning
confidence: 99%
“…(2) Declines are expected to be related to fire regimes, as these vary markedly across the northern Australian landscape and have changed considerably in both frequency and timing since European settlement (Braithwaite 1991;Crowley and Garnett 2000;Russell-Smith et al 2003a). The general trend has been for decreased frequency in pastoral areas and increased frequency in the higher-rainfall nonpastoral areas of the far north.…”
mentioning
confidence: 99%